Perencanaan Pengembangan Pengelolaan Sampah di Bantaran Sungai Alas Desa Kutacane Lama Kabupaten Aceh Tenggara - Rimandani Rimandani; Satia Negara Lubis; Charloq Charloq (Universitas Muhammadiyah Sumatera Utara, 2023)
This research tries to demonstrate the impact of Planning by proxy Evaluation of resources, Economic Aspects, Institutional Aspects and Location Aspects on waste management on the banks of the Kali Bulan River (Alas River) in Kutacane Lama Village,. This research approach is explanatory research by exploring the relationship of variables in a model. Data analysis technique uses Structural Equation Modeling PLS (SEM-PLS) in analyzing the model. The results of this research prove that planning from the Resource Evaluation Aspect influences Waste Management. Planning from the Economic Aspect has no effect on Waste Management. Planning from the Institutional Aspect has no significant effect on Waste Management. Planning from the Location Aspect influences Waste Management. The according to the findings of this study, it is advised to increase evaluation of resources from community participation, because the role of the community in efforts to improve waste management on river banks is an important aspect for the smooth implementation of waste management. The importance of full support from the regional government in implementing the waste management program through optimizing facilities and infrastructure in riverbank villages for a wider and more comprehensive range of waste services.Keywords: Waste Management, Resource Evaluation, Regional Planning.